PENINGKATAN KEMAMPUAN MENULIS DESKRIPSI DALAM PEMBELAJARAN BAHASA INDONESIA DENGAN MENGGUNAKAN MEDIA POSTER PADA SISWA KELAS V UPT SD NEGERI 1 CENTRE PATTALLASSANG - Gunawan Sofyan; Andi Paida; Muhammad Saeful (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The aim of this research is to determine the improvement in the ability to write descriptions in learning Indonesian using poster media for class V UPT SD Negeri 1 Center Pattallassang students. The benefits of research consist of theoretical benefits and practical benefits, namely for students, researchers, teachers and schools. This type of research is class action research (Class Action Research) which consists of two cycles where each cycle is carried out in four meetings. The focus of this research is 1) Skills in writing descriptive essays and 2) Use of poster media in class V UPT SD Negeri 1 Center Pattallassang. Research procedures include planning, implementing actions, observing and reflecting. The research subjects were 38 class V students. The collected data was analyzed using quantitative and qualitative analysis. The results of this research were that there was an increase in student learning activities from cycle I to cycle II, student learning outcomes experienced an increase, namely the average score of student learning outcomes in cycle I was 68, increasing in cycle II to 94. Students' learning to write descriptive essays also increased. , where in cycle I, 18 (47%) students achieved learning completeness, while in cycle II 38 (100%) students achieved learning completeness and classical learning completion was achieved. This means that learning completeness in cycle II was achieved classically because the number of students who completed it was more than 80%. Based on the results of the research above, it can be concluded that the skill of writing descriptive essays for class V UPT SD Negeri 1 Center Pattallassang through the application of poster media has increased.